Abnormal Heart Rate Recovery and Duke Treadmill Score as Predictor of Cardiovascular Mortality - YB Utomo (ACI (Acta Cardiologia Indonesiana), 2017)
Background: The Duke Treadmill Score (DTS) has been well validated and widely used for .....